IMPLEMENTASI PASAL 283 UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN TERHADAP PENGENDARA OJEK BERBASIS APLIKASI DI KOTA PEKANBARU - Reski Reski; Erdianto Effendi; Adi Tiara Putri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The progress of the transportation system has driven a person towards lifestyle, namely application-based transportation, called online transportation, which has been characterized by hatred for moving places, fluency in the exchange of goods and services, and the high level of employment and high social mobility. Motorcycle taxis have become alternative transportation for some people because they are flexible in their activities, can reach places that are not passed by public transportation such as city transportation, buses, or other types of four-wheeled public transportation.This type of research can be classified in the type of sociological legal research,because in this study the authors immediately conduct research on the location or place under study in order to provide a complete and clear picture of the problem under study. This research was conducted in Pekanbaru City, while the population and samples were Head of Unit Then in Pekanbaru City Police, Members of Pekanbaru City Police, application-based motorcycle taxi management in Pekanbaru City and application-based motorcycle taxi drivers in Pekanbaru City.The conclusion that can be obtained from the results of the study is the implementation of Article 283 of Law No. 22 of 2009 concerning traffic and road transportation for application-based motorcycle taxi drivers in the city of Pekanbaru has not yet proceeded as it should. Obstacles to the implementation of Article 283 of Law No. 22 of 2009 concerning traffic and road transportation for application-based motorcycle taxi drivers in Pekanbaru City in the form of law enforcement factors and effective and Driver Awareness Factor in this case the lack of awareness of the driver-based community about traffic regulations has the potential to cause traffic accidents. Efforts made to overcome the obstacles to the implementation of Article 283 of Law Number 22 of 2009 concerning traffic and road transportation for application-based motorcycle taxi riders in Pekanbaru City consist of Preventive and RepressiveKeywords: Application, Surcharge, Merchant, Consumers, Transactions, Credit Cards